Niveles de estrés y formas de afrontamiento en estudiantes de Medicina en comparación con estudiantes de otras escuelas - La Rosa-Rojas, Gessely de (2015)
Objective: To assess the levels of stress and the coping strategies in students of the faculties of Medicine, Law and Psychology at a private university in Lima. Materials and Methods: Cross-sectional analytic and comparative study involving three university careers. For data collection, the SISCO inventory for academic stress and the questionnaire of stress coping (CAE) were used. For inferential analysis, Spearman’s rank correlation coefficient, Kruskall Wallis and Dunn Test (multiple comparison post hoc) were used. Results: The average age was 19.5 ± 2.5 years. Of them, 33.9% were students from the Medical faculty and 92.4% were worried or nervous (stress manifestations). The students from the Medical faculty had the highest level of stress (median, 46.7) compared to the students from the Psychology faculty (median, 39.1) and the students from the Law faculty (median, 40.2) (p < 0.05). The most common coping strategies were focusing on the problem, positive re-evaluation, and social support. The least used strategy was religion. Conclusion: The Medical faculty students show the highest level of stress. Coping strategies in the three groups are focusing on the problem, positive re-evaluation, and social support